PENGEMBANGAN E-LKPD MENGGUNAKAN WEBSITE WIZER.ME PADA MATERI BUDAYA DAERAH INDONESIA - Putri, Fitriyah Adilah; Nurlinda Safitri; Santa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop E-LKPD (Electronic Student Worksheets) using the Wizer.me website on Indonesian regional culture material. This study uses a Research and Development approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were 28 fifth-grade students in class V-B at SDN Muara Beres Elementary School in Bogor Regency. The research was conducted in the even semester of the 2024/2025 academic year. In this study, a validation test was conducted by experts, namely media experts, language experts, and subject matter experts. The validation results by media experts obtained 100% with a very feasible criterion, by language experts obtained 88% with a very feasible criterion, by lecturer subject matter experts obtained 94% with a very feasible criterion, and by teacher subject matter experts obtained 96% with a very feasible criterion. The student response questionnaire results obtained 97.21% with a very feasible category, and the average N-Gain learning outcome score was 0.7 with a high criterion. These results indicate that E-LKPD using the Wizer.me website is very feasible to use in the learning process and very effective in improving student learning outcomes.